Pengaruh Massa Pada Beban Terhadap Konstanta Pegas - qurro taayun, hanifah; Malik, Adam (Al-Khazini: Jurnal Pendidikan Fisika, 2023)
A spring is an elastic object that provides deviation when loaded and returns to its original shape when the load is released. In this study using experimental methods and literature review, this experiment also uses variables and variables tied to a quantitative research approach. In determining the coefficient of elasticity, the spring is loaded with a load to show the proportional relationship between spring extension and weight. The proportionality coefficient is the spring elasticity coefficient. The purpose of the experiment was to determine the effect of the load mass on the spring constant. The result of the study is that the greater the gravity shared, the greater the length of the spring, and so is the length of the spring and the value of the constant. So the relationship between gravity and spring length is directly proportional. From the research that has been carried out, it can be concluded that the force exerted on the spring will cause the increase of the display on the spring, and this change is directly proportional